A Short Indel-Lacking-Resistance Gene Triggers Silencing of the Photosynthetic Machinery Components Through TYLCSV-Associated Endogenous siRNAs in Tomato - Chiumenti, Michela; Catacchio, Claudia Rita; Miozzi, Laura; Pirovano, Walter; Ventura, Mario; Pantaleo, Vitantonio (Frontiers in Plant Science, 2018)
Plant viruses modify gene expression in infected tissues by altering the micro (mi)RNA-mediated regulation of genes. Among conserved miRNA targets there are transcripts coding for transcription factors, RNA silencing core and disease resistance proteins. Paralogs in these gene families are widely present in plant genomes and are known to respond differently to miRNA-mediated regulation during plant virus infections. Using genome-wide approaches applied to Solanum lycopersicum infected by a nuclear-replicating virus, we highlighted miRNA-mediated cleavage events that could not be revealed in virus-free systems. Among them we confirmed miR6024 targeting and cleavage of RX-Coiled-coil (RX-CC), nucleotide binding site (NBS), leucine rich (LRR) mRNA. Cleavage of paralogs was associated with short indels close to the target sites, indicating a general functional significance of indels in fine-tuning gene expression in plant-virus interaction. miR6024-mediated cleavage, uniquely in virus-infected tissues, triggers the production of several 21-22nt secondary siRNAs. These secondary siRNAs, rather than being involved in the cascade regulation of other NBS-LRR paralogs, explained cleavages of several mRNAs annotated as defence-related proteins and components of the photosynthetic machinery. Outputs of these data explain part of the phenotype plasticity in plants, including the appearance of yellowing symptoms in the viral pathosystem.